Symbolic Miracles of the Qur’an (A Study on “Fenomenologi Alquran” by Luqman Abdul Qahar Sumabrata) | الإعجاز الرمزي للقرآن الكريم (دراسة في كتاب "Fenomenologi Alquran" عند الأستاذ لقمان عبد القهار سومابراتا) - Usman Syihab; Novrita Novrita (Al-Zahra : Journal for Islamic and Arabic Studies, 2021)
This research deals with the symbolic miracles of the Qur’an  in term of symbolic  meaning contained in the Qur’an, from letters, numbers, names of surah and juz according to Luqman Abdul Qahar Sumabrata in his book “Fenomenologi Alquran”. The research aims to know some symbols in the Qur’an and tries to reveals the philosophy and meaning for each of the symbols. Discovering the philosophy and meanings of the Qur’an’s symbols can help to expand the fields of Qur’anic sciences and to show more aspects of the miraculous of the Qur’an. This research uses the inductive-analytical method, a library method and personal interview and dialogue with Lukman’s students. Among the results of this research  are; that each of the elements in the Qur’an has a philosophy and a specific meaning related to the universe and humans, letters are the key to understanding the Qur'an, while numbers are the linking form of every elements which have dual forms and broad meanings. The research also reveals that names of surah and the arrangement of juz are depictions of cosmic and human psyche.